2023
DOI: 10.1515/jpem-2022-0598
|View full text |Cite
|
Sign up to set email alerts
|

Response to vitamin D replacement therapy in obese children and adolescents with vitamin D deficiency: a randomized controlled trial

Abstract: Objectives Vitamin D deficiency is common in the pediatric group with obesity and is a risk factor for metabolic syndrome. Supplementation of vitamin D may require higher dosing than in normal-weight children. The aim of our study was to investigate the response of supplementation on vitamin D levels and the metabolic profile in youths with obesity. Methods Children and adolescents with obesity (Body mass index >2.3 SDS, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…A recent randomised controlled trial showed that daily 6000 IU vitamin D supplementation in obese children was safe and sufficient to reach vitamin D sufficiency. 30 Increasing more aggressively in obese children could be taken into account when increasing dosages in these children does not resolve a previously identified vitamin D deficit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent randomised controlled trial showed that daily 6000 IU vitamin D supplementation in obese children was safe and sufficient to reach vitamin D sufficiency. 30 Increasing more aggressively in obese children could be taken into account when increasing dosages in these children does not resolve a previously identified vitamin D deficit.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomised controlled trial showed that daily 6000 IU vitamin D supplementation in obese children was safe and sufficient to reach vitamin D sufficiency. 30 Increasing Open access more aggressively in obese children could be taken into account when increasing dosages in these children does not resolve a previously identified vitamin D deficit. Finally, the strategy of increasing the dosage, which differed extensively between countries, when a VDI was measured, did not contribute to the risk of not resolving the VDI.…”
Section: Discussionmentioning
confidence: 99%